De la transferencia de conocimiento hacia el desempeño de la firma en el sector metalmecánico de Pereira (2021)
Globalization effects and its impacts in organizations have generated important transformations, in the way they establish their relations, exchange information, and the way they consider the knowledge in the territory. Specifically in the metal-mechanical sector and the Firm “Integrando Ltda.”, there are historical evidences on how a section of factories when it comes to information exchange and alliances experience with other enterprises, has generated knowledge appropiacy and a better local performance going from tacit understanding to explicit knowledge standards, which becomes basic in the transformation of the organizations. When using the methodology of multiple cases study (Yin,1994), it is necessary to know and diagnose the different cases of transference evidence compared with others that do not show significant levels. The first case study shows the experience of the firm “Integrando Ltda” in the Colombian city of Pereira.